2009
DOI: 10.1016/j.concog.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Level of agency in sub-clinical checking

Abstract: a b s t r a c tThis study examined cognitive representations of routine action, through the assessment of level of agency, in individuals with sub-clinical checking. The level of agency stems from Action Identification Theory [Vallacher, R. R., Wegner, D. M. (1989). Levels of personal agency: Individual variation in action identification. Journal of Personality and Social Psychology 57, 660-671], which states that how actions are usually identified (based on instrumental aspects or purpose) reflects the predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 34 publications
1
37
1
Order By: Relevance
“…First, our interpretation of the nature of the relationship found between experienced agency and checking symptoms is limited, as we did not control for the potential confounding effect of other factors, such as dissociation, anxiety, and attentional focus. For example, dissociative states, which are frequently associated with checking (Belayachi & Van der Linden, 2009;Rufer, Fricke, Held, Cremer, & Hand, 2006), can reduce awareness of action by altering the integration of action representations (e.g., expected effects) and the ''present self in action" (e.g., observed outcomes) (Ansfield & Wegner, 1996). Furthermore, several studies have emphasized the importance of attention focused on representations related to goals, expected effects or intention in action awareness, as compared to attention focused on movements (Lau, Rogers, Haggard, & Passingham, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…First, our interpretation of the nature of the relationship found between experienced agency and checking symptoms is limited, as we did not control for the potential confounding effect of other factors, such as dissociation, anxiety, and attentional focus. For example, dissociative states, which are frequently associated with checking (Belayachi & Van der Linden, 2009;Rufer, Fricke, Held, Cremer, & Hand, 2006), can reduce awareness of action by altering the integration of action representations (e.g., expected effects) and the ''present self in action" (e.g., observed outcomes) (Ansfield & Wegner, 1996). Furthermore, several studies have emphasized the importance of attention focused on representations related to goals, expected effects or intention in action awareness, as compared to attention focused on movements (Lau, Rogers, Haggard, & Passingham, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the level of action identification has been implicated in several psychopathological symptoms, including obsessive-compulsive behaviors (Belayachi & Van der Linden, 2009;Dar & Katz, 2005), autistic traits (Marsh et al, 2010) and impulsivity (Vallacher & Wegner, 1989). For example, people with checking symptoms have been related to a low level of action identification (Belayachi & Van der Linden, 2009). A lack of goal identification in checking individuals could explain the diminished sense of goal completion they frequently experience and their need to repeat actions regardless of the obvious achievement of the goal.…”
Section: Level Of Action Identificationmentioning
confidence: 99%
“…Based on reported evidence that the level of action identification may influence symptoms and mechanisms implied in various psychopathological symptoms, Watkins (2011) suggested that defective action identification may be a transdiagnostic process across psychological disorders. Indeed, the level of action identification has been implicated in several psychopathological symptoms, including obsessive-compulsive behaviors (Belayachi & Van der Linden, 2009;Dar & Katz, 2005), autistic traits (Marsh et al, 2010) and impulsivity (Vallacher & Wegner, 1989). For example, people with checking symptoms have been related to a low level of action identification (Belayachi & Van der Linden, 2009).…”
Section: Level Of Action Identificationmentioning
confidence: 99%
See 2 more Smart Citations